2015
DOI: 10.3791/52841
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Learning in Young Infants: Tracking Leg Actions During a Discovery-learning Task

Abstract: Task-specific actions emerge from spontaneous movement during infancy. It has been proposed that task-specific actions emerge through a discovery-learning process. Here a method is described in which 3-4 month old infants learn a task by discovery and their leg movements are captured to quantify the learning process. This discovery-learning task uses an infant activated mobile that rotates and plays music based on specified leg action of infants. Supine infants activate the mobile by moving their feet vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Interestingly, after a longer exposure, infants refined the necessary motor action and were able to make the actions in a more efficient manner. Similar observations were made in several other studies (e.g., Thelen, 1994; Angulo-Kinzler, 2001; Chen et al, 2002; Tiernan and Angulo-Barroso, 2008; Sargent et al, 2014, 2015), suggesting that infants’ exploration of sensorimotor contingencies might play a role in motor skill refinement. Developmental psychologists have also measured the influence of contingent feedback on the development of emerging skills such as reaching.…”
Section: Body Knowledge: Is the Agent Able To Identify The Particularsupporting
confidence: 89%
“…Interestingly, after a longer exposure, infants refined the necessary motor action and were able to make the actions in a more efficient manner. Similar observations were made in several other studies (e.g., Thelen, 1994; Angulo-Kinzler, 2001; Chen et al, 2002; Tiernan and Angulo-Barroso, 2008; Sargent et al, 2014, 2015), suggesting that infants’ exploration of sensorimotor contingencies might play a role in motor skill refinement. Developmental psychologists have also measured the influence of contingent feedback on the development of emerging skills such as reaching.…”
Section: Body Knowledge: Is the Agent Able To Identify The Particularsupporting
confidence: 89%
“…Interestingly, after a longer exposure, infants refined the necessary motor action and were able to make the actions in a more efficient manner. Similar observations were made in several other studies (e.g., Thelen, 1994;Angulo-Kinzler, 2001;Chen et al, 2002;Tiernan and Angulo-Barroso, 2008;Sargent et al, 2014;Sargent et al, 2015), suggesting that infants' exploration of sensorimotor contingencies might play a role in motor skill refinement. Developmental psychologists have also measured the influence of contingent feedback on the development of emerging skills such as reaching.…”
Section: Motor Skill Refinementsupporting
confidence: 89%
“…Some other researchers were specifically interested in the movement patterns when the mobile paradigm had specific task requirements. In these experimental designs, only the movements that satisfied particular criteria, such as the angle between the upper and lower leg exceeding a threshold (Thelen, 1994 ; Angulo-Kinzler and Horn, 2001 ; Angulo-Kinzler, 2001 ; Angulo-Kinzler et al, 2002 ; Tiernan and Angulo-Barroso, 2008 ), keeping the foot (Sargent et al, 2014 , 2015 ) or head (Tripathi et al, 2019 ) above a virtual threshold, and foot contact with a touch panel (Chen et al, 2002 ), were able to activate the mobile. For example, Angulo-Kinzler ( 2001 ) developed the constrained version of the mobile paradigm in which the legs of the infants activated the mobile only if the extension or flexion of the leg exceeded a particular angle threshold.…”
Section: Recent Yearsmentioning
confidence: 99%
“…Given that previous reports have indicated that not all infants can learn the contingency in the mobile paradigm (Gerhardstein et al, 2012 ; Jacquey et al, 2020a ), investigating behavioral differences between learners and non-learners has gained importance. In a study in which the mobile was activated only if the target leg exceeded a virtual threshold, infants who were able to learn the task exhibited different movement kinematics (e.g., less in-phase hip-knee coordination) compared to non-learners during the acquisition phase (Sargent et al, 2015 ). In another study in which the infants were required to move their heads above a virtual threshold, 50% of them did not satisfy the learning criteria (Tripathi et al, 2019 ).…”
Section: Recent Yearsmentioning
confidence: 99%